Anti-diabetic effects of natural antioxidants from fruits. (November 2021) - Sun, Chongde; Liu, Yilong; Zhan, Liuhuan; Rayat, Gina R.; Xiao, Jianbo; Jiang, Huamin; Li, Xian; Chen, Kunsong
Abstract: Background: Diabetes mellitus (DM), a chronic disease characterized by hyperglycemia, is an increasing global health problem which is associated with various chronic diseases such as hypertension, hyperlipidemia and cardiovascular diseases. Despite traditional insulin therapy, nutrients and nutritional factors are also known to play a significant role in the control and treatment of DM. Scope and approach: This comprehensive review focuses on recent advances in knowledge and understanding of the anti-diabetic effects of fruit consumption. Particular attention will be paid to natural antioxidants found in different fruits that may have anti-diabetic effects in human. Key findings and conclusions: Oxidative stress is an important cause and therapeutic target of DM. Plant-based food such as fruits are rich sources of natural antioxidants. Various epidemiological studies, clinical studies, in vivo and in vitro studies showed that fruits with different phytochemical profiles have the ability to lower blood glucose to normal levels. Bioactive compounds identified to have anti-diabetic activities include phenolic compounds, polysaccharides, vitamin C, and most of them have antioxidant activity or can induce antioxidant systems in different experimental models. Therefore, fruits are good resources of anti-diabetic nutrients and a balanced diet rich in different fruits is recommended for diabetic patients and the pre-diabetic population. Highlights: Oxidative stress is an important cause and therapeutic target of diabetes. Fruits are rich sources of natural antioxidants that possess anti-diabetic effects. Balance between oxidative stress and antioxidants are common mechanisms in alleviating DM in humans and stress in plants. A balanced diet rich in fruits is recommended for diabetic individuals and pre-diabetic population.